Jejunojejunal intussusception in an adult due to adenoma: a case report. Issue 7 (19th July 2022) - Subedi, Krishna P; Timilsina, Shashank; Yadav, Krishna Kumar; Shrestha, Suraj; Kansakar, Prasan B S
Abstract: Intussusception is a rare condition in adults and presents a diagnostic challenge. Clinical presentation tends to be chronic and non-specific. Unlike the pediatric population, most adult intussusceptions have structural lesions as lead points. Here, we present a case of jejunojejunal intussusception in a 27-year female due to adenoma of small bowel.